"One pot" microwave assisted synthesis of 5,10,15-tri(4-methoxyphenyl)-20-(4-chlorophentyl)-21H,23H-porphyrin and its zinc (II) complex - Loredo Calderón, Erika Lilián; Martínez Lejia, Carolina; López Cortina, Susana; Muñoz Flores, Blanca M.; Hernández Fernández, Eugenio; Jiménez Pérez, Víctor Manuel; Cuevas Yañez, Erick (Universidad Autónoma de Nuevo León, 2012)
The synthesis of new unsymmetrical A3B porphyrin, 5,10,15-tri(4-methoxyphenyl)-20-(4-chlorophentyl)-21H,23H-porphyrin, 1, and its zinc(II) complex, 5,10,15-tri(4-methoxyphenyl)-20-(4-chlorophentyl)-21,23-Zinc(II)-porphine, 2, was accomplished using both conventional and "one pot" solventless microwave assisted methods with interesting comparative results. The obtained molecules were characterized by H NMR, UV-Vis and MS. These molecules are considered to represent new compounds with potential application as photosensitizers in photodynamic therapy.